2010
DOI: 10.1038/clpt.2010.116
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Asymmetric Dimethylarginine in Chronic Heart Failure: A Pathophysiologic Link Between Oxygen Radical Load and Impaired Vasodilator Capacity and the Therapeutic Effect of Allopurinol

Abstract: Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide-dependent vasodilation. In 113 patients with chronic heart failure (CHF) and 26 controls, ADMA level was studied in relation to peripheral blood flow and vasodilator capacity. Further, the effects of allopurinol on concentrations of reactive oxygen species (ROS) and ADMA and peripheral vasodilator capacity were tested in a double-blind design. ADMA level was found to be elevated in CHF patients as compared with controls and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…[50][51][52] An indirect effect of allopurinol on regulation of vascular tone via interaction with asymmetric dimethylarginine has been observed. 53 In addition, multiple other pathophysiologic features in CVD were shown to be improved after XO inhibition (Table 1). From those proof-of-concept studies, further evidence has emerged that indeed XO activity rather than UA may be viewed as the true therapeutic target.…”
Section: Xo-derived Ros: Impact In Cvdmentioning
confidence: 99%
“…[50][51][52] An indirect effect of allopurinol on regulation of vascular tone via interaction with asymmetric dimethylarginine has been observed. 53 In addition, multiple other pathophysiologic features in CVD were shown to be improved after XO inhibition (Table 1). From those proof-of-concept studies, further evidence has emerged that indeed XO activity rather than UA may be viewed as the true therapeutic target.…”
Section: Xo-derived Ros: Impact In Cvdmentioning
confidence: 99%
“…46 The level of ADMA is suggested to predict survival in patients with chronic heart failure. 47 The plasma ADMA levels were higher in patients with typical exertional angina, positive exercise test, and normal coronary arteries diagnosed as cardiac syndrome X than in the control group, whereas plasma L-arginine levels were similar in both groups; patients with abnormal myocardial tissue perfusion had increased plasma ADMA levels compared with those with normal tissue perfusion. 48 In the patients with cardiac syndrome X, increased plasma ADMA levels may be associated with impaired myocardial tissue perfusion.…”
Section: 23mentioning
confidence: 93%
“…In patients with chronic heart failure, allopurinol lowered ROS and ADMA concentrations and improved postischemic vasodilatation and endothelium-dependent vasodilatation. 47 Recent studies by Noman et al 93 on patients with chronic stable angina showed that high-dose (600 mg/d) alloprinol increased the mean time to ST depression, median total exercise time, and the time to chest pain from the baseline. Alloprinol seems to be a useful, inexpensive, welltolerated, and safe anti-ischemic drug for patients with chronic stable angina.…”
mentioning
confidence: 99%
“…Among the patients undergoing treatments with allopurinol, the levels of plasma Malondialdehyde (MDA), extracellular superoxide dismutase (ecSOD) activity, allantoin, appeared to significantly reduced [18,19,21]. Furthermore, biomarkers of adaptive heart remodeling, Matrix metalloproteinases (MMPs) and Tissue inhibitors of metalloproteinases (TIMMPs), were evaluated without notable changes [15,18].…”
Section: P Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%
“…Completely different from above, endothelial function improvement benefited from allopurinol attracted great attention to itself, that 9 clinical trials chose it as an end-point was an evidence [11,14,16,18,[19][20][21][22]. Among these studies, endothelial function was directly evaluated by Forearm blood flow (FBF) or Flow-mediated dilation (FMD).…”
Section: P Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%